PENGARUH GAYA KEPEMIMPINAN DAN KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI : (Sensus Pada Perangkat Desa di Kecamatan Cimerak Kabupaten Pangandaran) - Hak, Cecep Abdul; Yusnita, Rita Tri; Rahwana, Kusuma Agdhi (Politeknik Negeri Ambon, 2023)
This study aims to determine the simultaneous and partial effect of Leadership Style and Work Ability on the Performance of Village Officials in Cimerak District, Pangandaran Regency. The research method used in this study is a quantitative method with an associative (causality) and census analysis approach. The population in this study amounted to 138 village officials in Cimerak District. The type of data used in this study is primary data obtained through questionnaires. The data testing technique used in this study uses the validity test, reliability test and classic assumption test. Data analysis in this study used multiple regression. The results of this study indicate that leadership style and work ability simultaneously have a significant effect on the performance of village officials in Cimerak District, Pangandaran Regency. Leadership Style partially has a significant effect on the performance of village officials in Cimerak District, Pangandaran Regency and Work Ability partially has a significant effect on the performance of village officials in Cimerak District, Pangandaran Regency.